Developing tools of short-term reliability evaluation using a fast sorting technique (FST) / Mohd Khairul Na'im Uyup - Uyup, Mohd Khairul Na'im (2009)
This project discusses the application of Fast Sorting Technique (FST) in order to evaluate the reliability of components, equipments or systems. The technique that have been developed by Institution of Engineering and Technology is considering the speed and accuracy requirements so this technique will quickly select the required number of systems state in descending order probability. After several calculations using sorting procedure, the stopping rule for the evaluation will be met. This stopping rule is defined as the relative accuracy of a given reliability index. Next, the value of Expected Demands Not Supply, EDNS is calculated using the appropriate equation. Fast Sorting Technique only needed a small number of system states to achieve the high accuracy of the short-terms reliability and this will take a minimum evaluation of comparisons and also the number of comparisons.